KETELADANAN GURU DALAM PEMBENTUKAN KARAKTER KEJUJURAN DAN KEDISIPLINAN PADA SISWA PAUD(SUATU TINJAUAN LITERATUR) - Andi Rosnawati (Pojok Publisher, 2025)
Early childhood is in a very important period of moral development, where teacher behavior becomes a concrete model for the formation of character values. This study aims to examine the role of teacher role models in the formation of honesty and discipline in early childhood students. This study was conducted with a literature study approach using a narrative model as a study framework. The results of the study found that Early Childhood Education (PAUD) is more than just academics, honesty and discipline as a foundation for the formation of student character, teachers as Models of Norms and Behavior and the existence of social aspects and Collective identity. Related to teacher role models from the literature review in instilling the values ​​of honesty and discipline play a role as the main pillar in early childhood character education. Role modeling is not just a method, but a holistic pedagogical approach that simultaneously addresses cognitive, affective, and psychomotor aspects. Therefore, the teacher's role as a role model is not complementary, but at the heart of character education.